The Effects of Mental Health and Substance Abuse/Dependence Disorders on Prison Misconduct Among Male Inmates in Taiwan - Kuo, Shih-Ya (International journal of offender therapy and comparative criminology, 2020)
This study examined the relative effects of mental illness, substance abuse/dependence, and co-occurring mental disorders and substance abuse/dependence (CODs) on prison misconduct among male inmates (N = 2,065) incarcerated in Taiwan’s nine correctional facilities. Both bivariate and multivariate analyses revealed that COD-affected inmates have the highest risk of prison misconduct compared to those with singular drug abuse/dependence disorders or no disorders, similar to the findings of previous studies conducted in the United States. These results highlighted the importance of clinical screenings and assessments for inmates who might have CODs. Integrated treatments may be more appropriate for inmates with CODs, rather than providing separate treatments for mental and drug abuse/dependence disorders.